Type 2 innate lymphoid cells treat and prevent acute gastrointestinal graft-versus-host disease - Bruce, Danny W.; Stefanski, Heather E.; Vincent, Benjamin G.; Dant, Trisha A.; Reisdorf, Shannon; Bommiasamy, Hemamalini; Serody, David A.; Wilson, Justin E.; Mckinnon, Karen P.; Shlomchik, Warren D.; Armistead, Paul M.; Ting, Jenny P. Y.; et al. (Journal of Clinical Investigation, 2017)
Acute graft-versus-host disease (aGVHD) is the most common complication for patients undergoing allogeneic stem cell transplantation. Despite extremely aggressive therapy targeting donor T cells, patients with grade III or greater aGVHD of the lower GI tract, who do not respond to therapy with corticosteroids, have a dismal prognosis. Thus, efforts to improve understanding of the function of local immune and non-immune cells in regulating the inflammatory process in the GI tract during aGVHD are needed. Here, we demonstrate, using murine models of allogeneic BMT, that type 2 innate lymphoid cells (ILC2s) in the lower GI tract are sensitive to conditioning therapy and show very limited ability to repopulate from donor bone marrow. Infusion of donor ILC2s was effective in reducing the lethality of aGVHD and in treating lower GI tract disease. ILC2 infusion was associated with reduced donor proinflammatory Th1 and Th17 cells, accumulation of donor myeloid-derived suppressor cells (MDSCs) mediated by ILC2 production of IL-13, improved GI tract barrier function, and a preserved graftversus-leukemia (GVL) response. Collectively, these findings suggest that infusion of donor ILC2s to restore gastrointestinal tract homeostasis may improve treatment of severe lower GI tract aGVHD.
CRIS-Team Scopus Importer:2023-03-23